De-Mystifying Saturated Fats – A Perspective - Mani, Indu; Kurpad, Anura V; Kurpad, Anura V (Indian Journal of Community Health, 2014)
Since the 1980s the world has been repeatedly informed about the harmful effects of saturated fatty acids. The USDA recommends that SFA consumption should be < 10 en%, while the American Heart Association goes a step further and suggests that the intakes should be reduced to < 7 en%. However, recent findings are increasingly questioning this advice, showing evidence that consumption of SFA may actually be better than increasing intake of either carbohydrates or polyunsaturated fatty acids. This article aims to summarize some of this information, with emphasis on its relevance to Indian diets.